2016
DOI: 10.1007/s00405-016-4183-2
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and comparison of gain values with occurrence of saccades in the EyeSeeCam video head impulse test (vHIT)

Abstract: VOR gain values and the occurrence of saccades in the diagram. Differences in gain values between examiners varied from 0.2 to 0.58 with an average of 0.14 (95 % CI 0.12-0.16) on the right ear and 0.17 (95 % CI 0.15-0.19) on the left ear. Occurrences of saccades in the same patient were reproduced in 93 % of the cases by all examiners. Kappa's coefficient on the occurrence of saccades was 0.83. Interclass correlation coefficient (ICC) of the gain values between examiners ranged from 0.62 to 0.70. Differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 13 publications
1
19
0
4
Order By: Relevance
“…Present study suggests the presence of refixation saccades can be reliably and repeatedly recorded when evaluating lateral SCC but not vertical SCC. A study by Korsager et al (2016) reported better reliability for the presence of refixation saccades than the VOR gain between the clinicians; however, this was shown only for the lateral SCC. Korsager et al (2016) did not examine the test-retest reliability of LARP and RALP, the measures that assess functioning of the vertical canals on either side.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Present study suggests the presence of refixation saccades can be reliably and repeatedly recorded when evaluating lateral SCC but not vertical SCC. A study by Korsager et al (2016) reported better reliability for the presence of refixation saccades than the VOR gain between the clinicians; however, this was shown only for the lateral SCC. Korsager et al (2016) did not examine the test-retest reliability of LARP and RALP, the measures that assess functioning of the vertical canals on either side.…”
Section: Discussionmentioning
confidence: 94%
“…A study by Korsager et al (2016) reported better reliability for the presence of refixation saccades than the VOR gain between the clinicians; however, this was shown only for the lateral SCC. Korsager et al (2016) did not examine the test-retest reliability of LARP and RALP, the measures that assess functioning of the vertical canals on either side. Therefore, the present study may be treated as an extension to their work with more details on vertical canals in addition to the lateral canal.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…RFS might occur during the head impulse or after the end of the head impulse and are referred to as covert and overt RFS [29]. RFSs are much more reliable than the VOR gain values in between different testers [41]. One problem is RFS, which increase in higher age without a VOR gain decrease and could clinically mimic a pathological vHIT [35].…”
Section: Video-head-impulse Test (Vhit)mentioning
confidence: 99%
“…In a previous study, we suggested that the refixation saccades might be a better predictor of the vestibular function than gain value (5). The gain value is known to vary for a number of reasons, whereas the occurrence of saccades seems more reliable.…”
Section: Discussionmentioning
confidence: 99%